Against progress: Understanding and resisting the temporality of transformational weight loss narratives. Issue 2 (4th May 2018) - Fox, Rachel
ABSTRACT: Narratives of personal transformation through weight loss, often presented in the form of before-and-after photos, have the power to bend time into a nonlinear structure that glorifies the future at the expense of the past and present. In this article, the author proposes that the temporality created by presenting weight loss as a way to perfect one's life is actually a manifestation of a larger, progress-driven temporality embedded in Western history and culture. An analysis of this larger temporality through its appearance in the colonial paradigm of progress and the queer studies concept of reproductive futurism provides a critical lens through which to examine its materialization in dieting discourse and internalization by fat dieters. This lens reveals that disillusioned dieters may have trouble giving up on their weight loss attempts because doing so involves rejecting a much larger temporal pattern. People who have given up on dieting may develop an ambivalent relationship to the present as they resist the temporality of transformational weight loss while continuing to live in a society built on a larger version of it.